Analisis Penulisan Preposisi pada Berita Media Center Kabupaten Indragiri Hilir - Fauziah, Fauziah (UIR PRESS, 2022)
The presence of the right preposition in a sentence will lead to attachment both from a grammatical and semantic perspective. If the use of prepositions is not appropriate in the sentence, there will be a blurring of the sentence structure and the meaning of the sentence. This research raises the problem, namely, how is the analysis of prepositional writing on Media Center news in Indragiri Hilir Regency? With a qualitative approach. The technique used is the hermeneutic technique. The theoretical reference in this study is Chaer (2009). From the results of processed data related to the Analysis of Writing Prepositions at Media Center News in Indragiri Hilir Regency, it is known that there are as many as 45 prepositional word data in Media Center News, Indragiri Hilir Regency. In this case, it is also known that the preposition in the sentence used to express